Análisis comparativo de los parámetros productivos en cerdos castrados mediante los métodos: quirúrgico e inmuno castración - Muñoz León, Cesar Abel (2025)
On the global stage, the significance of swine production in the agri-food industry is indisputable. The industry is a primary source of animal protein for human consumption, underscoring its fundamental role in global nutrition and sustainability. The primary objective of this study is to ascertain the productive parameters in pigs subjected to surgical or immunocastration, with a focus on evaluating their impact on animal welfare. This investigation aims to generate scientific information that will inform decision-making processes in the domain of swine production. The research was conducted in the swine production area to evaluate and compare the productive parameters between surgical castration and immuno-castration. A total of 20 male pigs of varying genetic backgrounds were utilized as subjects for study. The experimental procedures involved two distinct methods of castration: surgical and immunocastration. These methods differed in their approach to reproductive parameters. The most efficacious treatment was determined to be immunocastration or chemical castration. T2 exhibited superior outcomes in terms of weight gain (2354 lb), feed consumption (4400 lb), feed conversion (1.87), and benefit-cost ratio (3.12). These results surpassed those of surgical castration (T1), which yielded weight gain (2002 lb), feed consumption (5000 lb), feed conversion (2.49), and cost-benefit ratio (2.68). This analysis indicates a progressive increase. It is concluded that immunocastration, also known as T2 chemical castration, is a viable alternative to analyze and determine the productive characteristics and health of the animals. This method is comparable and even superior to surgical castration.